Chewing Function in Children with Repaired Esophageal Atresia–Tracheoesophageal Fistula - Serel Arslan, Selen; Demir, Numan; Karaduman, Aynur Ayşe; Tanyel, Feridun Cahit; Soyer, Tutku (European Journal of Pediatric Surgery, 2018)
Introduction Feeding problems are common in children with esophageal atresia and tracheoesophageal fistula (EA–TEF); however, chewing disorders, which may cause inability to intake solid food, have not been evaluated. Therefore, we aimed to evaluate the chewing function in children with repaired EA–TEF.Materials and Methods Age, sex, the type of atresia, the type of repair, and the time to start oral feeding were recorded. The level of the chewing performance was scored according to the Karaduman Chewing Performance Scale (KCPS). The International Dysphagia Diet Standardization Initiative (IDDSI) was used to determine the tolerated food texture in children.Results A group of 30 patients were included, of which 53.3% was male. The percentages of the isolated-EA and that of the EA–distal TEF were 40% and 60%, respectively. The median value for the time to start oral feeding was 4.5 weeks (min = 1, max = 72). Eleven (36.7%) children had chewing disorder. The KCPS scores showed level I in six cases, level III in four cases, and level IV in one case. Five children with chewing disorder had IDDSI level 3 and six had level 7, along with the sensation of stuck food. We found no significant difference between the KCPS scores according to the repair type (p = 0.07). The median values of the KCPS scores of children with primary repair, delayed repair, and colon interposition were 0 (min = 0, max = 4), 0.5 (min = 0, max = 3), 2 (min = 0, max = 3), respectively. A significant positive correlation was found between the time to start oral feeding and the KCPS scores (r = 0.63, p = 0.001).Conclusion Chewing disorders can be observed in children with EA–TEF, and the type of repair and the delay in oral feeding may be related to chewing disorder. Therapeutic maneuvers are needed to improve the chewing function in children with EA–TEF.
Keywords: esophageal atresia; tracheoesophageal fistula; chewing disorders; chewing function